Enhancing Quality of Guidance and Counseling in Vocational Schools: Testing the Effectiveness of Evaluation Instruments Based on the CIPP Model - Setiawan, Muhammad Andri; Sari, Nina Permata; Makaria, Eklys Cheseda; Dinanty, Najwa Shabrina; Rahman, Gazali (PAEDAGOGIA, 2024)
This study assesses the CIPP (Context, Input, Process, Product) model's effectiveness in evaluating guidance and counseling programs within the Merdeka curriculum of Vocational High Schools. Collaborating with three experts—guidance and counseling specialists, educational technology experts, and practitioner teachers—the research employs assessment tests and pre-test/post-test questionnaires for 10 Guidance and Counseling Teachers at Vocational High School 3 Banjarmasin. Evaluation results, covering general, specific, and material aspects, show a high level of agreement among the three evaluators. General evaluation exhibits high reliability (ICC = 0.750), and thorough and material evaluations demonstrate high reliability with ICC values of 0.794 each. The trial of 10 Guidance and Counseling Teachers reveals a significant improvement in their evaluation skills after implementing the CIPP model. Average post-test results are notably higher than pre-test, highlighting the positive impact of the CIPP evaluation model on enhancing these skills. The research concludes that the CIPP evaluation model is reliable and consistent in measuring guidance and counseling program effectiveness in the Merdeka curriculum of Vocational High Schools. Empirical and theoretical support establishes a strong foundation for considering future implementation of the CIPP model in educational program evaluations. This model's application is anticipated to elevate the quality and relevance of educational programs, particularly in the context of guidance and counseling in Vocational High Schools, with potential practical and managerial benefits.